Microhabitat Influence on Growth Distribution Pattern of Ramin (Gonystylus bancanus) in Siak, Riau Province - Pribadi, Didit Okta; Kusuma, Yayan Wahyu C. (BIOTROPIA, 2015)
Plant growth distribution patterns are influenced by distribution of habitat characteristics, capacity of adaptation, and association with other plant species or animals. Global climate change has serious impact on the changing habitat which eventually threat plants. This study has objectives: (1) to measure plant growth dependence on their microhabitat; (2) to define microhabitat variables that influence growth significantly; and (3) to formulate suitable conservation efforts for certain species.Â Gonystylus bancanus is one of major timber species that has been facing high exploitation in Indonesia. This species is usually found on specific â€œpeat swampsâ€ ecosystem. Data were collected through primary surveys in Riau Province.Â Data analyses were peformed by clustering the adult base on variable of height and width of basalt area, and describing distribution pattern of the cluster. Then, Discriminant Function Analysis was used to overlay the cluster with the distribution of microhabitat characteristic consisting of altitude, slope, soil humidity, soil pH, peat depth and percentage of canopy cover. The result shows, distribution of microhabitat match with 67.4% of height distribution and 78.3% of width distribution of basalt area.Â Altitude and canopy cover percentage have significant correlation with height distribution (Î±=0.05).Â Meanwhile, altitude, canopy cover, and slope have significant correlation with width distribution of basalt area (Î±=0.1).Â However, peat depth variable shows interesting pattern since shallower peat depth are followed by wider of basalt area. High correlation between plant growth and its microhabitat suggests that in-situ conservation is better strategy than ex-situ conservation and this is particularly true for Gonystylus bancanus conservation management